Risk of Inter-Related Health Issues among Children with ASD in Bangladesh (Global Journal of Medical Research, 2015)
In recent time, autism has become a major concern, globally. Due to its rapid growth, the healthcare professionals and medical researchers have been relentlessly working to identify the causes of ASD (Autism Spectrum Disorder); though the reasons are still unclear. In light of the contemporary research paradigm on ASD, the inter-related health issues of ASD also have raised significant concerns in the field. It is very recent that the researchers are interested in the dimensions and dynamics of inter-related health issues among people with ASD. Keeping in mind the global research advancements, this empirical research focuses on exploring and examining inter-related health issues among the children with autism in Bangladesh. The results of this research clearly show that there is evidence of various forms of inter-related health issues among the children with autism in Bangladesh.
Keywords: autism; autism spectrum disorder; ASD; inter-related health issues and autism